Survival and growth of Mimosa caesalpiniaefolia seedlings on a Red-Yellow Podzolic soil under simulated erosion - Silva, José Ronaldo Coelho (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this research was to determine changes in properties of a Red-Yellow Podzolic soil, related to the gradual removal of the plow layer through simulated erosion and its effects on survival and growth of Mimosa caesalpiniaefolia Benth seedlings. In 1990, the experiment was conducted in a greenhouse of the Universidade Federal do Ceará, in Fortaleza, CE, Brazil, in layers of 0-15, 5-20, 10-25, 15-30, 20-35 and 25-40 cm which were removed from a Red-Yellow Podzolic profile and contained in plastic bags where seeds were planted and seedlings were grown for 85 days. Higher values of clay percentage, available water, K and Ca contents and of CEC at deeper layers did not reduce the negative impact of erosion on the seedlings survival and growth since they were associated with increases of Al saturation as well as with significant decreases in pH, organic matter, base saturation and N, P and Mg contents in the soil. As depth of the removed layers increased, seedlings survival percentage, seedlings height, root and aerial part dry weights, as well as total dry biomass gradually decreased. Compared to the 0-15 cm layer, at 25-40 cm those decreases were 16.8, 66.3, 67.1, 82.0, and 79.6%, respectively.